THE ROLE OF THE LYMPHATIC SYSTEM IN THE UVEOSCLERAL OUTFLOW OF AQUEOUS HUMOR - V. V. Chernykh; Y. I. Borodin; N. P. Bgatova; A. N. Trunov; N. S. Khodjayev; I. B. Druzhinin; A. V. Eremina; A. A. Pozhidaeva; V. I. Konenkov (Офтальмохирургия, 2015)
Purpose. To identify and study an organization of structures providing the lymphatic drainage of aqueous humor in the anterior chamber of the human eye.Material and methods. The eye fragments enucleated for medical reasons (n=5) were used as research objects. Electron microscopic and immunohistochemical study of eye tissues was carried out.Results. The organ-specific lymphatic capillaries in the ciliary body and structured interstitial spaces – tissue gaps bounded by collagen fibers and fibroblasts in the anterior segment of the human eye were revealed by using immunohistochemical and electron microscopy studies.Conclusions. It is proposed to consider the lymphatic region of the eye where on the basis of the obtained data the first 2 links were allocated - tissue gaps – prelymphatics and lymphatic capillaries of the ciliary body. Structured pathways of aqueous humor outflow can determine the eye trophic and drainage status, intraocular pressure and the function of the ocular organ.